Pyridinic nitrogen dominated doping on Pd/carbon catalysts for enhanced hydrogenation performance - He, Limin; Wang, Yangdong; Wang, Can; Liu, Zhicheng; Xie, Zaiku (Frontiers in Chemistry, 2022)
The hydrogenation of 4-carboxylbenzaldehyde over Pd catalysts is a crucial process during the production of pure terephthalic acid. Herein, ZIF-8 derived carbon materials (NC) with adjustable N types were synthesized and used as the supports of Pd catalysts. Pd supported on NC with 50.5% of pyridinic N exhibited best hydrogenation activity with a TOF value of 4.1 min-1. The microstructures of NC support and electronic structures of Pd in Pd/NC were investigated by techniques such as XRD, N2 physisorption, XPS, H2-O2 titration and TEM. The nitrogen species in CN surface not only can adjust chemical state and dispersion of Pd nanoparticles (NPs), but also promote the adsorption and activation capability of H2 molecular. Besides, the ratio of Pd0/Pd2+ and Pd dispersion were closely correlated with pyridinic nitrogen content. The improvement in hydrogenation activity and stability of Pd/CN catalyst in relative to Pd/C were ascribed to the synergistic effect of pyridinic nitrogen and active site Pd0.